Five-dimensional Fama-French Model test in analyzing common stock returns using profitability and investment (Entrepreneurship Journal for Finance and Business, 2023)
The research explores to test the Fama-French five-dimensional model in analyzing the returns of ordinary shares using profitability and investment as a measure of the model. Financial data needed for research. To solve the research problem, some mathematical laws and related statistical methods were adopted to analyze the data of the companies covered by the research. The results of the research indicated that the factors of profitability and investment, respectively, are the most important factors affecting the returns of the shares of the sample companies and their market value, on the one hand, and on the other hand, it requires the use of a five-dimensional Fama-French model to analyze the returns of ordinary shares from companies and the clarity and transparency of their financial information so that The financial analyst can use this model and rely on it in estimating stock returns, in addition to the existence of an efficient market in which the research sample companies operate, in addition to the ability of the F-F-5 model to explain the returns of the shares of the research sample companies by (67%), and this indicates that it contains (67%) ) of the risk factors that accompany its investment.Keywords: profitability, investment, stock returns, Fama-French five-dimensional model